THE EFFECTS OF YOGA ON INSOMNIA PATIENTS AMONG URBAN POPULATION -CHENNAI- A QUASI-EXPERIMENTAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Insomnia is a highly prevalent condition among the elderly as well as people above 40years of age. Insomnia can affect health (both mental and physical), day-to-day life activities, quality of daily life and in general, it affects overall wellbeing of life. Poor sleep quality could be because of physical and psychological stress, agerelated physiological changes, chronic comorbidities, and lifestyle changes. Consumption of medications is the most commonly used treatment, but it can lead to dependency and have many adverse effects. Therefore, as an interventional method that is non-pharmacological and cost-effective, yoga has gained significant attention among insomnia patients. Yoga has been shown to reduce anxiety and physiologic arousal through a multidimensional practice consisting of specific postures, breathing exercises and a philosophical attitude[1] Objective: To evaluate the effectiveness of a structured yoga intervention in improving sleep quality and reducing insomnia and related symptoms among elderly individuals in an urban population Methodology: A Pre and Post interventional assessment conducted to a study group of 60 elderly people with sleep related complaints. A total of 3 months of intervention of yoga were given and sleep parameters were assessed using a set of standardised questions.  Results: This study validated a considerable improvement of sleep parameters after the intervention. The finding of the data indicates a persistent reduction in mean scores of the data and a p value